Development of a Learning Tool using the Cooperative Integrated Reading and Composition (CIRC) Model Based on Thunkable - Elvi Mailani; Daitin Tarigan; Andri Kristanto Sitanggang (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to develop a Thunkable-based cooperative, integrated reading and composition (CIRC) model for mathematics instructional development in Unimed's PGSD program. Classroom observations revealed that current teaching practices inadequately engage students in fostering reading interest and substantive discussions for mathematical understanding. The study seeks to enhance pedagogical practices by integrating reading diversification through a Thunkable-based instructional framework. The research's overarching objective is to craft a CIRC-guided learning apparatus, utilizing Thunkable for the mathematics instructional development course in Unimed's PGSD program. Following Sugiyono's four-D model, the study employs a Research and Development approach encompassing the Define, Design, Develop, and Disseminate stages. Anticipated outcomes include obligatory deliverables like a comprehensive report, indexed proceedings publication, research proposal copyright, and publication in an accredited national journal. Supplementary outputs comprise an ISBN-endowed book, potential copyright or patent, and international journal publication. This research advances mathematics pedagogy within Unimed's PGSD program by integrating cooperative learning and technology-enhanced reading practices via Thunkable. Such an approach aligns with the progressive paradigm of educational development, fostering a conducive environment for comprehensive learning experiences and meaningful academic discourse.